2016
DOI: 10.1080/15384101.2016.1199305
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus Mcm10 is a CDK-substrate required for replication fork stability

Abstract: During S phase, following activation of the S phase CDKs and the DBF4-dependent kinases (DDK), double hexamers of Mcm2-7 at licensed replication origins are activated to form the core replicative helicase. Mcm10 is one of several proteins that have been implicated from work in yeasts to play a role in forming a mature replisome during the initiation process. Mcm10 has also been proposed to play a role in promoting replisome stability after initiation has taken place. The role of Mcm10 is particularly unclear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 68 publications
(78 reference statements)
4
42
0
Order By: Relevance
“…S1 A). Among genes whose KO selectively impaired proliferation of ETAA1Δ cells, we identified several factors with known roles in promoting DNA synthesis, including MCM10, POLE3, POLE4, and CDC25A (Bartek et al, 2004;Chadha et al, 2016;Bellelli et al, 2018), while sgRNAs targeting essential DNA replication factors including proliferating cell nuclear antigen and CMG helicase subunits were depleted in both WT and ETAA1Δ cells as expected (Fig. 1, B and C; Fig.…”
Section: Resultssupporting
confidence: 77%
“…S1 A). Among genes whose KO selectively impaired proliferation of ETAA1Δ cells, we identified several factors with known roles in promoting DNA synthesis, including MCM10, POLE3, POLE4, and CDC25A (Bartek et al, 2004;Chadha et al, 2016;Bellelli et al, 2018), while sgRNAs targeting essential DNA replication factors including proliferating cell nuclear antigen and CMG helicase subunits were depleted in both WT and ETAA1Δ cells as expected (Fig. 1, B and C; Fig.…”
Section: Resultssupporting
confidence: 77%
“…MCM10 reportedly plays a role in tethering DNA polymerase α at the replication origin and forks. Studies using Xenopus egg extracts indicated that Mcm10 plays an essential role as a scaffold in the progression of the DNA replication fork by tethering replication proteins, and phosphorylation of Mcm10 at S630 with CDK is involved in protein assembly at the fork (Chadha et al, 2016). In elongation during DNA replication, Mcm10 is required for gene silencing and chromosomal condensation (Apger et al, 2010).…”
Section: Muta�onmentioning
confidence: 99%
“…Furthermore, recruitment of Mcm10 is dependent on Cdc45, GINS, DDK, and S-CDK (7,8). Recent results obtained in a Xenopus egg extract system also support that chromatin loading of Mcm10 requires DDK and S-CDK (45).…”
mentioning
confidence: 58%